ASSOCIATION OF A NEMATODE CERATOSOLENIUS RACEMOSA GEN. N. SP.N (CYLINDROCORPORIDAE : RHABDITIDA GOODEY, 1939) A WASP (CERATOSOLEN SP.N.) AND FIG FICUS RACEMOSA - ANAND, L. RAJESWAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
The association of cylindrocorporid nematode species with a fig pollinating Wasp Ceratosolen sp. in the figs of Ficus racemosa is studied. The new genus Ceratosolenus sp. is erected to accommodate the nematode Ceratosolenus racemosa. The new genus differs from other members of the family Cylindrocorporidae, in lacking winged lepoderan tail, caudal papillae and caudal alae in males. The biology of the nematode is also discussed.